2014
DOI: 10.1038/ncomms4797
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive classification of microcalcifications with phase-contrast X-ray mammography

Abstract: Microcalcifications can be indicative in the diagnosis of early breast cancer. Here we report a non-invasive diagnostic method that may potentially distinguish between different types of microcalcifications using X-ray phase-contrast imaging. Our approach exploits the complementary nature of the absorption and small-angle scattering signals of microcalcifications, obtained simultaneously with an X-ray grating interferometer on a conventional X-ray tube. We demonstrate that the new approach has 100% sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
118
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 24 publications
2
118
1
Order By: Relevance
“…Application of SAXS and WAXS in vivo is also very difficult due to the high X-ray dose required for signal detection, because the primary X-ray beam is blocked and the signal is only generated from the scattered X-ray photons, which are several orders of magnitude less than the transmitted ones. However, X-ray phase-contrast methods based on gratingbased dark-field imaging [164,288] could be more easily adopted to be used in vivo in animals [221,289] and eventually in humans [290,291], whereas they can also be combined with standard X-ray absorption methods [223,292]. Their use in providing information on ultrastructure organization [161,169], by exploiting ultrastructure orientation-dependent signal modulations [168,293], is expected to rise in the future, as these methods have not been adequately explored to date [169].…”
Section: In Vivo Assessmentmentioning
confidence: 99%
“…Application of SAXS and WAXS in vivo is also very difficult due to the high X-ray dose required for signal detection, because the primary X-ray beam is blocked and the signal is only generated from the scattered X-ray photons, which are several orders of magnitude less than the transmitted ones. However, X-ray phase-contrast methods based on gratingbased dark-field imaging [164,288] could be more easily adopted to be used in vivo in animals [221,289] and eventually in humans [290,291], whereas they can also be combined with standard X-ray absorption methods [223,292]. Their use in providing information on ultrastructure organization [161,169], by exploiting ultrastructure orientation-dependent signal modulations [168,293], is expected to rise in the future, as these methods have not been adequately explored to date [169].…”
Section: In Vivo Assessmentmentioning
confidence: 99%
“…This approach to quantitative XPCI was proven to work under extremely weak coherence conditions, and uses the full broadband spectrum typically produced by an X-ray tube. It simultaneously produces three representations of the sample that can provide complementary information for better identification and discrimination between materials and types of tissues [26][27][28]. The work presented here builds on these results, focusing on the expansion of the method to include system imperfections that can be encountered in practical situations and the exploitation of a priori knowledge that might be available about the sample.…”
Section: Introductionmentioning
confidence: 99%
“…This signal component is called dark field contrast. 6 In the context of the application to mammography, it has been shown that the x-ray dark-field contrast can be used to detect microcalcificationsan important indicator for breast cancer-even before they are visible in the conventional attenuation contrast image 13 and that it can be used to distinguish between different types of calcifications, 14 which is an important information for the differentiation between benign and malignant tumors. As of today, it remains to be investigated whether differential phasecontrast imaging is compatible with full-field digital mammography (FFDM) in terms of the mechanical stability, achievable field-of-view (FOV), and scan time.…”
Section: Introductionmentioning
confidence: 99%